A survey on factors affecting fuel smart card user acceptance and security - Eslami, Seyed Gholamereza (2010)
Smart card technology is one of the strong computer revolutions among the fast growing usage of new technologies. Due to widespread distribution of smart card, a special type of smart card has been applied for the fuel system that is used nowadays by most vehicles’ owners in Iran. Due to the advantages of the fuel smart card such as managing fuel quota by optimizing using fuel quota and preventing from smuggling is becoming popular among vehicles’ owners in Iran. In this master project report the user acceptance and security factors of fuel smart card have been evaluated. Acceptance factor based on adoption model involved many factors such as: satisfaction, security, external variables, attitude toward using, and adoption. In this report have been evaluated acceptance and security factors of the fuel smart card technology by distributing questionnaire among UTM (University Technology Malaysia) Iranian students and MMU (Multimedia University) Iranian students, either asking by e-mail from people who are not available. Based on preliminary results security is most important factor for the fuel smart card users.